Production of poly-β-1,6-N-acetylglucosamine by MatAB is required for hyphal aggregation and hydrophilic surface adhesion by Streptomyces - van Dissel, Dino (Microb Cell, 2018)
Streptomycetes are multicellular filamentous microorganisms, and major producers of industrial enzymes and bioactive compounds such as antibiotics and anticancer drugs. The mycelial lifestyle plays an important role in the productivity during industrial fermentations. The hyphae of liquid-grown streptomycetes can self-aggregate into pellets, which hampers their industrial exploitation. Here we show that the Mat complex, which is required for pellet formation, catalyzes the synthesis of extracellular poly-β-1,6-N-acetylglucosamine (PNAG) in the model organisms Streptomyces coelicolor and Streptomyces lividans. Extracellular accumulation of PNAG allows Streptomyces to attach to hydrophilic surfaces, while attachment to hydrophobic surfaces requires a cellulase-degradable extracellular polymer (EPS) produced by CslA. Over-expression of matAB was sufficient to restore pellet formation to cslA null mutants of S. lividans. The two EPS systems together increase the robustness of mycelial pellets. These new insights allow better control of liquid-culture morphology of streptomycetes, which may be harnessed to improve growth and industrial exploitation of these highly versatile natural product and enzyme producers.